General discussion: Multiphase atmospheric chemistry, and source apportionment - Alshammari, Danah; Bloss, William; Chen, Ying; Chow, Judith C.; Gani, Shahzad; Harrison, Roy; Hu, Dawei; Li, Guo; McFiggans, Gordon; Oyarzún Aravena, Andrea María; Aravena, Andrea M. Oyarzun; Pfrang, Christian; et al. (My University, 2021)
Ying Chen opened the discussion of the paper by Guo Li: I have a question regarding your outdoor chamber. I see in the paper (DOI: 10.1039/d0fd00099j) you mention McFAN introduced an outdoor chamber experiment. May I ask what scientific question you want to answer by using this unique chamber?
Keywords: Apportionment